The cost-effectiveness of glasdegib in combination with low-dose cytarabine, for the treatment of newly diagnosed acute myeloid leukemia in adult patients who are not eligible to receive intensive induction chemotherapy in Canada. (1st January 2021) - Hu, Yannan; Charaan, Majed; van Oostrum, Ilse; Heeg, Bart; Bell, Timothy
Abstract: Aim: The clinical efficacy and safety of DAURISMO (glasdegib) combined with low-dose cytarabine (LDAC) were demonstrated in the BRIGHT AML 1003 study among newly diagnosed acute myeloid leukemia patients who are not eligible to receive intensive chemotherapy. This study aims to evaluate its cost-effectiveness versus LDAC alone and azacitidine from a Canadian payer perspective. Materials and Methods: A partitioned-survival model was developed with three health states: progression-free survival (PFS), relapse/progression and death. Clinical inputs were obtained from the BRIGHT AML 1003 study for glasdegib and LDAC, and from the two trial publications and indirect treatment comparison for azacitidine. Drug acquisition/administration, disease management, adverse event and end-of-life costs were considered. All costs were measured in Canadian dollars. Cost-effectiveness of glasdegib + LDAC was assessed against LDAC alone in main population, and against azacitidine by bone marrow blasts (BMB). A weighted average ICER was calculated to represent the current treatment use of Canadian clinical practice. The reference-case analysis was conducted probabilistically, and numerous probabilistic scenario analyses were conducted. Results: The incremental cost-effectiveness ratios (ICERs) compared to LDAC alone was CAD 177, 065 (a mean gain of 0.41 QALYs and an incremental cost of CAD 72, 695), to azacitidine in 20–30% and >30% BMB group were CAD 178, 201 (a mean gain of 0.34 QALYs and an incremental cost of CAD 59, 889) and dominant (a mean gain of 0.28 QALYs while reducing costs by CAD 7, 856) respectively, resulting in a weighted average ICER of CAD 81, 310 per QALY. Limitations and conclusions: Though uncertainties remain with the generated PFS curve, the derived azacitidine curves, administration and vial wastage, the model has been built under the best available evidence and relied on clinical opinions where there were data gaps. The weighted average ICER suggests that glasdegib + LDAC is cost-effective at a CAD 100, 000 willingness-to-pay threshold.